Radial force variation parameter as a factor of tire uniformity - Moskwa, Marcin; Gapiński, Bartosz; Jakubowicz, Michał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Market demands and trends related to ecology and sustainability significantly influence various industries, including the tire market. Tires are required to meet multiple performance criteria, such as braking efficiency, wet grip, and noise levels, while also conforming to uniformity parameters evaluated during the manufacturing process. Increasing the fuel efficiency of tires, which is directly related to reducing rolling resistance, results in a modification of tire materials, dimensions, and weight. As a result, components with lighter properties are used in tire construction, and at the same time, tires are subjected to higher loads. Research indicates that the green tire building process at the tire building machine has a key impact on the values and waveform of the tire radial force. The methodology of this study involved introducing controlled changes in the angular alignment of the individual drums participating in the green tire assembly process. This approach enabled the isolation and analysis of specific factors contributing to the shaping of the radial force variation (RFV) characteristics. For each configuration, a sample population of 20 tires was evaluated, with measurements taken for both RFV and waveform values. From these measurements, average RFV characteristics were generated. Each resulting characteristic was then compared to a reference specification in order to quantify the influence of the modified angular positions on RFV values and waveform behavior.